Nomenclatural notes on Isodon glaucocalyx and segregation from Isodon japonicus (Lamiaceae) - T. S., Alan; T. P., Krishnaraj; P., Sunojkumar (Phytotaxa, 2024)
The Isodon genus comprises 100 species and is predominantly distributed in tropical and subtropical regions throughout Asia. The current study highlights the necessity of addressing the nomenclatural problem concerning Isodon japonicus and Isodon glaucocalyx. In 1832, Bentham treated Scutellaria japonica as the synonym of Plectranthus coetsa. Consequently, in some Indian botanical literature, P. coetsa is referred to as P. japonicus. Later, P. coetsa along with S. japonica was included as synonyms of P. glaucocalyx var. japonicus and due to publication priority resulting in I. glaucocalyx being considered a variety of I. japonicus, even though they are distinct species.